Enabling technologies for utilization of maize as a bioenergy feedstock. (21st November 2019) - Choudhary, Mukesh; Singh, Alla; Gupta, Mamta; Rakshit, Sujay
Abstract: Limited supplies of fossil fuels have led to a search for alternative sources of fuel to drive economic growth. Maize, and especially the grain portion, has been utilized to a large extent for biofuel production while the abundant lignocellulosic portion has remained underexplored owing to its recalcitrant nature. The diversion of grain for bioethanol production has consequences for food security. However, the lignocellulosic portion can easily be directed for ethanol production without any consequences for food security. Maize has emerged as the leading crop in the last decade and hence provides a vast amount of grain and biomass. Biomass quantity and its digestibility are the two key traits for efficient biofuel production. Significant variation has been reported for these traits in maize. The brown midrib mutants ( bm ) of maize, with reduced lignin content, can be exploited for the development of cultivars with better digestibility. Recent advances in genetics and genomics revealed key genomic regions associated with biomass‐contributing traits. The molecular markers associated with the identified genomic regions can be utilized for marker‐aided development of cultivars with high biomass and better digestibility. Advances in phenomics have also facilitated bioethanol‐targeted breeding in maize. Biorefining uses feedstock as input and processes it into biofuel. In this review, the improvement of maize as a feedstock and biological conversion strategies of lignocellulosic biomass are assessed. Research and development platforms to enable improvements in feedstock and biological processing are also discussed. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.